An analytical study of some determinants of criminal behavior in Syria (Journal of Hama University, 2025)
This research examined the impact that some economic and social factors can play on crime rates in Syria. This is done by studying per capita income measured by per capita GDP, unemployment rates, and divorce rates in Syria during the period from 2000 to 2021, in addition to applying some simple statistical methods such as multiple linear regression using the Evios program. Through this study, we found that per capita income and divorce rates did not have a statistically significant impact on crime rates, while unemployment rates had a statistically significant impact on crime rates.The explanation for this may be due to the definition of culture criminology, which is a systematic theoretical study of crime that seeks to understand crime in its cultural context. It views crime and crime-fighting institutions as cultural products. Culture criminology seeks to shed light on how influence influences the construction of crime, such as making and breaking laws, interacting with moral initiative, innovation, and aggression, and thus crime and its control are thought to be shaped by means determined by culture.